345 INTRAOCULAR TOXICITY STUDY OF A NOVEL CRYSTAL LIPID PRO-DRUG 5-FU FOR ANTI-PROLIFERATIVE RETINOPATHY IN THE RABBIT EYE. (1st January 2005) - Wu, Y. K.; Cheng, L.; Freeman, W. R.
Abstract : Purpose: This study sets out to test the toxicity and determine the highest non-toxic dose of a novel drug, hexadecyloxypropyl-phospho-5-fluro-2'-deoxyuridine (HDP-P-5F2'DU), as a potential agent for treatment of proliferative retinopathy. Properties attributed to an ideal intraocular injectable drug are long half-life, ease of administration, and minimal retina toxicity. Currently, many pharmaceutical agents for retinal diseases have systemic toxicities due to high dosage required to achieve adequate vitreous levels and the need for frequent dosing due to the their short vitreous half-life. HDP-P-5F2'DU is derived by adding a long carbon chain to the sugar of phospho-5-fluro-2'-deoxyuridine to achieve increased hydrophobic property. The hypothesis is that this will prolong its vitreous half-life without losing therapeutic efficacy. Methods: 12 New Zealand red rabbits were divided into 4 treatment groups of 3 rabbits each. HDP-P-5F2'DU was added into the diluent and diluted into 4 stock concentrations. The right eye of each rabbit received 50μl of drug stock solution, while the left eye received a comparable volume of saline. Final drug concentrations for groups 1, 2, 3 and 4 were 5{152g/ml, 25152}g/ml, 50μg/ml and 250μg/ml respectively. Clinical exams of each eye were made prior to injection, 24 hours and every week after surgery. Anterior segment and fundus findings, vitreous clarity and distribution of drug aggregates within vitreous were documented using slit-lamp and indirect ophthalmoscope. At 6 weeks after injection, the 2 low dosage groups were sacrificed because of the gradual disappearance of drug aggregates. Electroretinography (ERG) was performed and 100 μl of vitreous fluid sampled prior to sacrifice. The eyes were enucleated and fixed for histopathology. The 2 higher dose groups are observed because of persistence of drug aggregates. Results: Clinical examinations of the 3 lower dose groups revealed no cataracts or retinal toxicity when compared to the saline-injected left eye. However, the highest dose group (250μg/ml) showed significant toxicity including retinal damage, cataracts of the lens, and iritis. ERG data for the two lower doses showed no difference between drug and control eyes. Vitreous drug measurement and histological sections of the retina are not yet available. The two higher dosage groups will be sacrificed this week. Clinical data suggests HDP-P-5F2'DU at 50μg/ml or lower doses to be safe for intravitreal use. Persistence of drug aggregates at 10 weeks suggests a half-life significantly longer than current drugs. Forthcoming vitreous tap and pathology data will provide more information about the drug's safety and potential efficacy.